Word Choice and Language Style of the Novel ‘Rahwana Putih' in Improving 21st Century Student Literacy - Herawati, Nanik; Setiyadi, Dwi Bambang Putut; Hersulastuti; Santoso, Gunawan Budi; Widayanti, Sukasih Ratna (Jurnal Pendidikan Indonesia, 2025)
The lack of students' ability to understand literacy in novels. This problem reflects the low interest of students in learning Indonesian and their difficulties in understanding literary works containing complex language. With the analysis of lexical choices and language styles in the novel "Rahwana Putih" by Sri Teddy Rasudi and its impact on student literacy in the 21st century. The urgency of this study lies in the importance of language factors in the development of students' analytical skills. The purpose of this study was to investigate the impact of lexical choices and linguistic styles on students' understanding. The method used is a mixed approach and the research population is 9th grade students in Klaten City totaling 1,600 students. Samples were taken randomly and 60 students were observed and interviewed. Data collection techniques were carried out through questionnaires and in-depth interviews, while data analysis was carried out through coding to identify themes and patterns from student responses. The results of the study showed that understanding and mastery of vocabulary choices and language styles contributed significantly to the development of student literacy. The conclusion of this study confirms that the analysis of language elements in literary works is important for improving students' reading comprehension and critical awareness and implications for the development of language and literature study curriculum in schools.